A quantitative analysis of the relationship between posttraumatic growth, depression and coping styles after burn. Issue 8 (December 2021) - Martin, Lisa; Rea, Suzanne; Wood, Fiona
Highlights: Coping style is related to posttraumatic growth and depression after burn. Positive framing, acceptance, religion predicts posttraumatic growth after burn. Venting, self-blame, behavioural disengagement predicts depression after burn. Abstract: Introduction: Posttraumatic growth (PTG) is "the subjective experience of positive psychological change reported by an individual as a result of the struggle with trauma" (Zoellner and Maercker, 2006 [1]). PTG after burn is similar to PTG after other types of trauma (Martin et al., 2016 [2]). The aim was to assess the relationship between coping styles, via the BriefCOPE (Carver et al., 1989 [9]), and posttraumatic growth via the Posttraumatic Growth Inventory (Cann et al., 2010 [4]), in an adult burn population. Method: 36 burn patients who required surgery for wound closure were recruited within 2 years of their burn. They completed the PTGI, DASS-D, and BriefCOPE, and again one month later. Regression analysis with backwards elimination assessed the relationships between coping styles, depression and posttraumatic growth. Results: Of the 14 coping types identified in the BriefCOPE, three were associated with PTG after burn: positive reframing, religion and acceptance. Three coping strategies were associated with greater levels of depression: behavioural disengagement, venting and self-blame. Conclusion: Behavioural disengagement, venting and self-blame behaviours can be used as 'red flags' to trigger early screening for depression and to enable timely treatment of depression. To maximise posttraumatic growth interventions that promote positive reframing, use of religion, and acceptance are necessary.